ChatGPT and Its Impact on Students Assessment Practices in the Higher Educational Sector: A Systematic Review - Ofusori, Lizzy Oluwatoyin; Hendradi, Rimuljo (Universitas Airlangga, 2025)
Background: The proliferation of Artificial Intelligence (AI) tools such as ChatGPT is growing at a rapid pace, sparing no sector. One of the AI tools that has grown in it use across the sectors is the use of ChatGPT, a tool that mimics human like capabilities of producing ideas. However, there have been many concerns about how ChatGPT will change the higher education institutions. More worrisome is how it poses risks that compromise the integrity of academic outputs if left unregulated Objective: This study examines the influence of ChatGPT on students’ assessment practices in the higher educational sector Methods: The study carried out a systematic literature review by gathering data from peer reviewed academic papers. Initially, 140 research papers were identified. Thereafter, these papers went through further filtering, and 35 usable papers were selected and included in the study Results: This study highlighted the importance of using AI tools such as ChatGPT in the higher education sector, underscoring its advantages and the threats that it poses to the sector if the use remains unregulated. The study has recommended institutional policies about the use of AI tools that must be put in place to guide academic staff, researchers and learners in the responsible use of ChatGPT for academic work. Conclusion: “While the widespread adoption of ChatGPT is undeniable, there is an urgent need for a well-balanced regulation regarding its use within Higher Education Institutions (HEIs). Thus, future research should focus on examining the existing policies and practices related to ChatGPT ethics, privacy, and security in education and identify gaps and areas for improvement. Keywords: ChatGPT, Artificial Intelligence, Chatbot, OpenAI, Higher Education